Metastatic Pulmonary Adenocarcinoma 13 Years After Curative Resection for Pancreatic Cancer: Report of a Case and Review of Japanese Literature - Kitasato, Yuhei; Nakayama, Masamichi; Akasu, Gen; Yoshitomi, Munehiro; Mikagi, Kazuhiro; Maruyama, Yuichiro; Kawahara, Ryuichi; Ishikawa, Hiroto; Hisaka, Toru; Yasunaga, Masafumi; Horiuchi, Hiroyuki; Saito, Naoyuki; et al. (JOP. Journal of the Pancreas, 2012)
Context For the majority of patients, ductal adenocarcinoma of the pancreas remains a lethal disease. Currently, surgical extirpation for localized disease offers the only chance for long-term survival. Case report We report a patient who underwent successful resection of isolated lung metastasis occurring 13 years after pancreatic cancer resection. A 59-year-old woman underwent distal pancreatectomy for pancreatic cancer 13 years previously, followed by adjuvant chemotherapy, and was followed-up at the outpatient clinic of a local hospital. From around June 2010, she noticed bloody sputum, so she visited a local hospital. Since her chest X-ray and CT revealed a 1.5 cm mass shadow in the segment 10 of her right lung and she was referred to the Respiratory Disease Center of our hospital. As a result of through examinations, she was strongly suspected of having lung metastasis of pancreatic cancer, and underwent partial pneumonectomy. Postoperative histopathological examination of the resected specimen was consistent with lung metastasis of pancreatic cancer. She is still alive and currently receives third line of chemotherapy. Conclusion Patients who have achieved long-term survival after pancreatic cancer resection and can tolerate surgery may benefit from resection of a lung metastasis of pancreatic cancer in terms of survival, if it controls the metastasis.